Mode of delivery, perinatal outcome and neurodevelopment in uncomplicated monochorionic diamniotic twins: a single-center retrospective cohort study - Angel Chimenea; Lutgardo García-Díaz; Guillermo Antiñolo (BMC, 2022)
Abstract Background There is no agreement on the effect of planned mode of delivery in the perinatal morbidity and neurodevelopment in uncomplicated monochorionic diamniotic as well as regarding the safest mode of delivery. In this paper we have aimed to analyze the impact of the mode of delivery in uncomplicated monochorionic diamniotic twins ≥ 32 weeks of gestation. Material and methods This study included 72 women, followed and attended at our department, with uncomplicated monochorionic diamniotic pregnancies who had a birth between 32.0 and 37.6 weeks of gestation from January 2012 to December 2018. Outcomes were recorded in women who underwent planned vaginal delivery (induced or spontaneous onset of labor), and women who underwent a planned cesarean section for any reason that excluded vaginal delivery. Primary outcomes included: (1) A composite of any of the following: neonatal death, 5-min Apgar score < 4, respiratory distress syndrome, bronchopulmonary dysplasia, sepsis, periventricular leukomalacia, intraventricular hemorrhage, and necrotizing enterocolitis. (2) Neurodevelopmental status at 2 years of corrected age. Results In this period, 42 women (58.3%) had a planned vaginal delivery, and 30 women (41.7%) had a planned cesarean section. In the first group, 64.3% had a vaginal delivery. The rate of successful vaginal delivery was similar regardless the onset of labor. We did not find a higher composite perinatal morbidity in the planned vaginal delivery group (planned vaginal delivery: 3.6% vs. planned cesarean section: 8.3%, aOR 1.36, 95% CI 0.24-7.81). Considering the onset of labor, it was more frequent in the spontaneous subgroup (8.3% vs. 0%). The rate of neurodevelopmental impairment was higher in the planned cesarean section group, without reaching statistical significance [10.2% vs. 4.9%, aOR 1.53 (95% CI 0.37-6.29)]. Conclusions In uncomplicated monochorionic diamniotic twins at ≥ 32 weeks of gestation, when the first twin is in vertex presentation, our results suggest that planned vaginal delivery is safe, with a successful outcome as well as high vaginal delivery rate.